Strain-Specific Transfer of Antibiotic Resistance from an Environmental Plasmid to Foodborne Pathogens. (27th June 2012) - Van Meervenne, Eva; Van Coillie, Els; Kerckhof, Frederiek-Maarten; Devlieghere, Frank; Herman, Lieve; De Gelder, Leen S. P.; Top, Eva M.; Boon, Nico
Abstract : Pathogens resistant to multiple antibiotics are rapidly emerging, entailing important consequences for human health. This study investigated if the broad-host-range multiresistance plasmid pB10, isolated from a wastewater treatment plant, harbouring amoxicillin, streptomycin, sulfonamide, and tetracycline resistance genes, was transferable to the foodborne pathogens Salmonella spp. or E. coli O157:H7 and how this transfer alters the phenotype of the recipients. The transfer ratio was determined by both plating and flow cytometry. Antibiotic resistance profiles were determined for both recipients and transconjugants using the disk diffusion method. For 14 of the 15 recipient strains, transconjugants were detected. Based on plating, transfer ratios were between6.8 × 10 − 9 and3.0 × 10 − 2 while using flow cytometry, transfer ratios were between <1.0 × 10 − 5 and1.9 × 10 − 2 . With a few exceptions, the transconjugants showed phenotypically increased resistance, indicating that most of the transferred resistance genes were expressed. In summary, we showed that an environmental plasmid can be transferred into foodborne pathogenic bacteria at high transfer ratios. However, the transfer ratio seemed to be recipient strain dependent. Moreover, the newly acquired resistance genes could turn antibiotic susceptible strains into resistant ones, paving the way to compromise human health.